1995
DOI: 10.1557/proc-388-85
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Highly Doped P-Type Znte Films by Pulsed Laser ablation in Molecular Nitrogen

Abstract: is DISCLAIMERPortions of this document may be illegible in electronic image products. Images are produced from the best available original document. GROWTH OF HIGHLY DOPED i-TYPE ZnTe FILMS BY PULSED LASER ABLATION IN MOLECULAR NITROGEN ABSTRACTHighly p-doped ZnTe films have been grown on semi-insulating GaAs (001) substrates by pulsed-laser ablation (PLA) of a stoichiometric ZnTe target in a high-purity N2 ambient without the use o any assisting (DC or AC) plasma source. Free hole concentrations in the mid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1995
1995
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…On the other hand, when a nitrogen glow discharge was established between parallel Cu plates in the same chamber, strong near-infrared N+ atomic emission lines and an N2+ emission band were seen. 7 The lack of atomic N emission from the PLA plasma in our experiments contrasts with the recent observation by Vaudo et al22 of strong near-IR atomic N lines emitted from the nitrogen plasma produced by an F W source that is used for N-doping during MBE growth. They concluded that atomic N (not molecular N2) is responsible for RF plasma p-type doping of ZnSe (and ZnTe) under MBE growth conditions.22 Our experiments do not directly rule out the presence of atomic N in the ground state during PLA, but this seems unlikely.…”
Section: Mechanism For Nitrogen Doping During Pulsed Laser Ablationcontrasting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, when a nitrogen glow discharge was established between parallel Cu plates in the same chamber, strong near-infrared N+ atomic emission lines and an N2+ emission band were seen. 7 The lack of atomic N emission from the PLA plasma in our experiments contrasts with the recent observation by Vaudo et al22 of strong near-IR atomic N lines emitted from the nitrogen plasma produced by an F W source that is used for N-doping during MBE growth. They concluded that atomic N (not molecular N2) is responsible for RF plasma p-type doping of ZnSe (and ZnTe) under MBE growth conditions.22 Our experiments do not directly rule out the presence of atomic N in the ground state during PLA, but this seems unlikely.…”
Section: Mechanism For Nitrogen Doping During Pulsed Laser Ablationcontrasting
confidence: 90%
“…This striking correlation suggests that the fast (vacuum) pulse of unscattered ions and atoms has sufficient kinetic energy to produce lattice displacement damage and point defects that reduce the hole mobility. 7 In another paper of this symposium19 Rouleau et al characteristic velocity and amplitude, were required to fit the ion probe data. For mode 1 (the vacuum or collision-free ion pulse in Fig.…”
Section: Effect Of Ambient Gas Pressure: Changes In the Dominant Filmmentioning
confidence: 99%
“…The formation of Ga compounds (e.g., Ga 2 Se 3 ) at the ZnSe/GaAs interface is thermodynamically favored and has been reported [16,17]. Further, it is known that Ga diffusion during the growth of ZnTe on GaSb leads to autodoping during PLD growth [18]. If this is occurring during the growth of our films, then the presence of Ga in the region near the ZnSe/GaAs interface may be responsible for the observed reduction in in-plane order.…”
Section: Discussionmentioning
confidence: 99%